Au-Pd nanoparticles-decorated TiO2 nanobelts for photocatalytic degradation of antibiotic levofloxacin in aqueous solution. (20th December 2015) - Chen, Qinghua; Xin, Yanjun; Zhu, Xiangwei
Highlights: The original photocatalyst Au-Pd/TiO2 NBs were synthesized by electrodeposition. Au-Pd/TiO2 NBs showed excellent photocatalytic activity. The LEV in aqueous solution can be degraded by Au-Pd/TiO2 NBs. Abstract: Novel TiO2 nanobelts decorated by bimetallic Au-Pd nanoparticles (Au-Pd/TiO2 NBs) were synthesized and used in photocatalytic (PC) degradation of antibiotic levofloxacin (LEV) in aqueous solution. The TiO2 NBs were prepared by potentiostatic anodization and the Au-Pd nanoparticles were assembled by electrodeposition. The structure and properties of Au-Pd/TiO2 NBs were well characterized by SEM, TEM, XRD, XPS, UV–vis DRS and photoelectrochemistry (PECH). The results of SEM and TEM revealed that perfect belt-like structure with 50–100 nm in width and several micrometres in length were formed. Au-Pd bimetallic nanoparticles with diameter from 5 to 10 nm were immobilized on the surface of TiO2 NBs. The results of UV–vis DRS and PECH showed that the Au-Pd/TiO2 NBs photocatalyst showed enhanced visible light absorption and lower recombination rate of electron-hole pairs compared with naked TiO2 NBs. The PC activity of Au-Pd/TiO2 NBs was evaluated by monitoring the decomposition of RhB in aqueous solution under simulated solar light, and results indicated that the Au-Pd/TiO2 NBs exhibited higher PC activity. The PC degradation efficiency of LEV can reach nearly 95% after 60 min of simulated solar light irradiation, and about 93% after 100 min of visible light irradiation. The decrease of PC degradation efficiency was found to be approximately 8% after 5 catalytic runs, indicating that Au-Pd/TiO2 NBs have super reusability. The scavenger study showed that OH, O 2 − and H2 O2 were the main active species involved in the PC degradation of LEV.